Synthesis of 2-Aminopyridine-Modified Peptide Nucleic Acids - Kumpina, Ilze; Baskevics, Vladislavs; Walby, Grant D.; Tessier, Brandon R.; Saei, Sara Farshineh; Ryan, Christopher A.; MacKay, James A.; Katkevics, Martins; Rozners, Eriks (Synlett, 2023)
Triplex-forming peptide nucleic acids (PNAs) require chemical modifications for efficient sequence-specific recognition of DNA and RNA at physiological pH. Our research groups have developed 2-aminopyridine (M) as an effective mimic of protonated cytosine in C+•G-C triplets. M-modified PNAs have a high binding affinity and sequence specificity as well as promising biological properties for improving PNA applications. This communication reports the optimization of synthetic procedures that give PNA M monomer in seven steps, with minimal need for column chromatography and in good yields and high purity. The optimized route uses inexpensive reagents and easily performed reactions, which will be useful for the broad community of nucleic acid chemists. Thought has also been given to the potential for future development of industrial syntheses of M monomers.
Keywords: peptide nucleic acids; aminopyridine; RNA recognition; triple helix; solid-phase synthesis